Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Pasien Hemodialisis - Siti Fadlilah (Politeknik Kesehatan Tanjung Karang, 2019)
The incidence of kidney failure worldwide continues to increase. Kidney failure patients are dependent on hemodialysis therapy. The implementation of hemodialysis therapy 2-3 times a week for 3-4 hours will cause boredom and boredom. This will affect the quality of life of patients with chronic kidney failure. This study to determine the relationship of age, sex, education, duration of hemodialysis, source of support, and family support to the quality of life of hemodialysis patients in Panembahan Senopati General Hospital Bantul Yogyakarta. This research used descriptive correlational with cross sectional approach. The samples were patients undergoing hemodialysis therapy at Panembahan Senopati Regional General Hospital Bantul taken by accidental sampling amounting to 71 respondents. Data collecting used a questionnaire. Bivariate analysis used the Spearman Rank statistical test. Most of the respondents were age range 46-60 years as many as 48 people (67.6%), male sex as many as 40 people (56.3%, high school education as many as 33 people (46, 5%), duration of 1-3 years hemodialysis range as many as 46 people (64.8%), and sources of support from husband/wife as many as 40 people (56.3%). Most respondents were getting enough family support as many as 31 people (43.7%) and adequate quality of life of 35 people (49.3%). Bivariate analysis of age, sex, education, duration of hemodialysis, and family support with quality of life obtained p-value 0.027; 0.758; 0.004; 0.093 0.015; and 0.000. There was a significant relationship between age, education, hemodialysis duration, and family support for the quality of life of hemodialysis patients in Panembahan Senopati Regional General Hospital, Bantul. While gender and source of support had no relation to the quality of life of hemodialysis patients in Panembahan Senopati Regional General Hospital Bantul.